Psalm 132 and its compositional context(s) - Human, Dirk J. (Scriptura, 2017)
Psalm 132 can be interpreted from various compositional contexts. In every new compositional context different nuances add value to the significance of the text. Psalm 132 can be interpreted as a single psalm, and as part of the Sire Hama 'alót psalms in smaller (130-134) or larger (120-134) collections. Finally the psalm can be understood as part of the theology and coherence of Book V (107-150) of the Psalter. The combination of Psalmen- and Psalterexegese therefore does not exclude each other, but they function complementarily. Both enrich the exegetical process and together they unveil the multiple theological perspectives connected to the different compositional contexts of a psalm.
free